Evaluation of three heterologous xylose isomerase genes for the fermentation of plant biomass to bioethanol in Saccharomyces cerevisiae - Robinson, Evan J (Department of Molecular and Cell Biology, 2024)
Diminishing oil reserves are causing scientists to explore renewable and sustainable replacement fuel sources. One candidate is plant biomass, although without modification its energy-rich sugars remain unavailable to the standard industrial yeast Saccharomyces cerevisiae for fermentation to the fuel ethanol. In this study, three xylose isomerase genes originating from Haemophilus influenzae Rd K20, Arabidopsis thaliana and Bacteroides thetaiotaomicron VPI-5482 were expressed in S. cerevisiae to produce a strain capable of metabolising D-xylose (a biomass constituent). Resulting strains were analysed for protein production, growth differences and xylose isomerisation but no introduced characteristics were detected. RT-PCR suggested transcription occurred for all the genes tested but no recombinant protein nor any xylose isomerase activity was detected. An in silico bioinformatic analysis showed a putative inhibitory stem-loop structure in the mRNA containing the B. thetaiotaomicron gene which may have reduced translation. Otherwise non-functional folding or undetectable activity were concluded as the results of the expression for all genes.